The Synergy of Artificial Intelligence and Pancasila Values in Realizing the Golden Indonesia 2045 - Elsa Dian Taimenas; Maria S. Lou Kelen (Public Policy : Jurnal Aplikasi Kebijakan Publik dan Bisnis, 2026)
The development of artificial intelligence has significantly influenced the mindset, behavior, and social interactions of the younger generation, particularly generation z, while posing challenges to the preservation of Pancasila values. The widespread use of digital platforms driven by artificial intelligence tends to promote sensational and individualistic content, contributing to a decline in the understanding and practice of collective values such as cooperation, unity, and social justice. This study aims to examine the impact of artificial intelligence on the practice of Pancasila values, identify factors contributing to value shifts, and formulate relevant digital-based educational strategies. Employing an interpretive qualitative approach, the research involves student participants and utilizes in-depth interviews, group discussions, and digital observations, with thematic analysis applied to ensure comprehensive and nuanced findings.